Assessment of molecular markers for anti-malarial drug resistance after the introduction and scale-up of malaria control interventions in western Kenya - Shah, Monica (Malar J, 2015)
BACKGROUND: Although it is well known that drug pressure selects for drug-resistant parasites, the role of transmission reduction by insecticide-treated bed nets (ITNs) on drug resistance remains unclear. In this study, the drug resistance profile of current and previous first-line anti-malarials in Kenya was assessed within the context of drug policy change and scale-up of ITNs. National first-line treatment changed from chloroquine (CQ) to sulphadoxine-pyrimethamine (SP) in 1998 and to artemether-lumefantrine (AL) in 2004. ITN use was scaled-up in the Asembo, Gem and Karemo areas of western Kenya in 1997, 1999 and 2006, respectively. METHODS: Smear-positive samples (N = 253) collected from a 2007 cross-sectional survey among children in Asembo, Gem and Karemo were genotyped for mutations in pfcrt and pfmdr1 (CQ), dhfr and dhps (SP), and at pfmdr-N86 and the gene copy number in pfmdr1 (lumefantrine). Results were compared among the three geographic areas in 2007 and to retrospective molecular data from children in Asembo in 2001. RESULTS: In 2007, 69 and 85% of samples harboured the pfmdr1-86Y mutation and dhfr/dhps quintuple mutant, respectively, with no significant differences by study area. However, the prevalence of the pfcrt-76T mutation differed significantly among areas (p <0.02), between 76 and 94%, with the highest prevalence in Asembo. Several 2007 samples carried mutations at dhfr-164L, dhps-436A, or dhps-613T. From 2001 to 2007, there were significant increases in the pfcrt-76T mutation from 82 to 94% (p <0.03), dhfr/dhps quintuple mutant from 62 to 82% (p <0.03), and an increase in the septuple CQ and SP combined mutant haplotype, K(76)Y(86)I(51)R(59)N(108)G(437)E(540), from 28 to 39%. The prevalence of the pfmdr1-86Y mutation remained unchanged. All samples were single copy for pfmdr1. CONCLUSIONS: Molecular markers associated with lumefantrine resistance were not detected in 2007. More recent samples will be needed to detect any selective effects by AL. The prevalence of CQ and SP resistance markers increased from 2001 to 2007 in the absence of changes in transmission intensity. In 2007, only the prevalence of pfcrt-76T mutation differed among study areas of varying transmission intensity. Resistant parasites were most likely selected by sustained drug pressure from the continued use of CQ, SP, and mechanistically similar drugs, such as amodiaquine and cotrimoxazole. There was no clear evidence that differences in transmission intensity, as a result of ITN scale-up, influenced the prevalence of drug resistance molecular markers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-015-0588-4) contains supplementary material, which is available to authorized users.